Periodontal and Systemic Diseases: Shared Pathophysiology - Najafimakhsoos, Neda; Cesari, Claudio (Trends in Immunotherapy, 2025)
Periodontitis is a chronic, progressive inflammatory disease characterized by the gradual destruction of the supporting structures of the teeth, including the periodontal ligament and alveolar bone. This condition primarily originates from microbial dysbiosis in the oral cavity, further influenced by the host’s immune responses and a variety of environmental and behavioral factors. As the leading cause of tooth loss and edentulism among adults, periodontitis also has far-reaching systemic consequences. An expanding body of scientific evidence has established strong associations between periodontitis and numerous systemic conditions, including cardiovascular disease, diabetes mellitus, respiratory disorders, thyroid dysfunction, and obstructive sleep apnea (OSA). This review examines the potential biological and clinical connections between periodontitis and these systemic diseases by first providing an overview of the normal physiological functions and pathological changes of each condition. It then explores the shared immunological and pathophysiological pathways, with particular focus on inflammatory mediators, immune system dysregulation, and microbial translocation. By integrating perspectives from disciplines such as microbiology, immunology, and clinical research, this review underscores the integral role of oral health in systemic well-being. It also highlights the necessity of early detection, interdisciplinary cooperation, and preventive strategies—including lifestyle modifications—to manage common risk factors and improve comprehensive patient outcomes.